Secrets of lost empires. Pyramid ; Obelisk [videorecording (DVD)] - Barnes, Michael (WGBH Boston Video, 2006)
Television programs about the building of the Great Pyramid at Giza and the construction of Egyptian obelisks. Archaeological teams test construction hypotheses using traditional building techniques.